2005
DOI: 10.1016/j.tics.2005.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The simultaneous chain: a new approach to serial learning

Abstract: Recent advances have allowed the application of behaviorism's rigor to the control of complex cognitive tasks in animals. This article examines recent research on serially organized behavior in animals. 'Chaining theory', the traditional approach to the study of such behavior, reduces intelligent action to sequences of discrete stimulus-response units in which each overt response is evoked by a particular stimulus. However, such theories are too weak to explain many forms of serially organized cognition, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 52 publications
6
97
0
Order By: Relevance
“…For instance, when pigeons are trained to respond to sequences with an A-B-C-D structure (the letters depicting different image categories), they respond more quickly when they see new strings in which the category items are in the original ordinal position than when they see strings in which the category items are switched (e.g., A-C-B-D) (45,46). A similar mapping of items to positions in both string-discrimination and food-localization paradigms has been noted in several primate species (20,47,48). While the positional learning as observed in the zebra finches is thus not uncommon, the detailed memory for item positions that they demonstrate in the current experiment is impressive, as they kept track of item positions over a set of ten training strings.…”
Section: Discussionmentioning
confidence: 53%
“…For instance, when pigeons are trained to respond to sequences with an A-B-C-D structure (the letters depicting different image categories), they respond more quickly when they see new strings in which the category items are in the original ordinal position than when they see strings in which the category items are switched (e.g., A-C-B-D) (45,46). A similar mapping of items to positions in both string-discrimination and food-localization paradigms has been noted in several primate species (20,47,48). While the positional learning as observed in the zebra finches is thus not uncommon, the detailed memory for item positions that they demonstrate in the current experiment is impressive, as they kept track of item positions over a set of ten training strings.…”
Section: Discussionmentioning
confidence: 53%
“…Even in the first three sessions of the first test block (filled circles, Figure 5), the birds responded fastest to pairs that were at the top of List X (A > B and B > C) and slowest to the last two pairs of List Y (3 > 4 and 4 > 5). Terrace (2005) has suggested that this pattern of increasing latency with distance from the top of the hierarchy is diagnostic of a relational representation.…”
Section: Discussionmentioning
confidence: 99%
“…However, such tasks reveal little about the strategy subjects use to perform an action sequence. For instance, because subjects are provided with discriminative cues that signal the identity of the response to be performed next, they may come to solve the task by learning a set of simple stimulus-response associations rather than by encoding the entire sequence of actions (Terrace, 2005). Alternatively, action sequence learning may be aided by the capacity to construct, or chunk, hierarchical action representations out of more elementary units of behavior (Lashley, 1951;Miller et al, 1960;Rosenbaum et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…For example, obtaining a goal often involves performing a sequence of two or more discrete actions. Although rats and other animals can be trained to perform action sequences of this kind, there is considerable debate about what is learned in such tasks (Terrace, 2005). One possibility is that the entire sequence becomes represented (perhaps through an action chunking process) as an integrated unit of behavior capable of entering into associations with discriminative cues and/or rewards (Lashley, 1951;Miller et al, 1960;Rosenbaum et al, 1983).…”
Section: Introductionmentioning
confidence: 99%